A study of the effect of natural radiation damage in a zircon crystal using thermoluminescence, fission track etching and X-ray diffraction - Amin, Y.M. (Elsevier, 1989)
The natural radiation damage in zircon caused by the decay of uranium and thorium, present as impurities, is studied, The radiation damage is first gauged by etching the fission tracks. It is found that thermoluminescence (TL) sensitivity (defined as light output per unit test-dose) decreases as the radiation damage increases, suggesting a destruction of TL centres. The spacing d of the (112)-plane is also measured. It is also found that the d-value increases with radiation damage, suggesting the displacement of atoms from their normal lattice sites. However, as the track density increases beyond ∼ 3 × 106 tracks/cm2, the d-value remains at . By annealing the crystal, the displaced atoms are found to return to the original lattice sites, and this is followed by a reduction in d-value as well as the recovery of TL sensitivity. The fission track density also decreases and all the tracks disappear at the annealing temperature of ∼ 800°C.